Pendidikan Kritis dan Strategi Authentic Learning: Studi Konsep Pendidikan KH. Ahmad Dahlan dan Paulo Freire - Achmad Hidayatullah; Sandha Soemantri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
Education in Indonesia has not fully solved the social problems. Therefore, there should be improvement of the education quality. The notion of KH. Ahmad Dahlan and Paulo Freire can be used as models in the implementation of education in Indonesia in order to be able to solve the social problems. This study aims to describe the concept of KH. Ahmad Dahlan and Paulo Freire in education including the big idea of ​​the concept of education and its implementation in the learning that includes learning strategies, approaches and methods. This study uses qualitative approach and literature study as its research method. The data were obtained through collecting some artifacts, documents and other relevant articles. Finally, this study provides four points as conclusions. First, both KH. Ahmad Dahlan and Paulo Freire used the concept of critical education. Second, the strategy used to implement educational ideas is authentic learning strategy. They led their students into experienced phenomena. Third, both of them chose student center learning approach, or learning that focuses on students. Fourth, the method used was dialogue. The four points are obviously relevant to the current implementation of education system in Indonesia. Conceptually, the learning strategy, approach, as well as method used by the two figures are in line with the 2013 curriculum.